2012
DOI: 10.1002/hyp.9358
|View full text |Cite
|
Sign up to set email alerts
|

Total waterborne carbon export and DOC composition from ten nested subarctic peatland catchments—importance of peatland cover, groundwater influence, and inter‐annual variability of precipitation patterns

Abstract: Waterborne carbon (C) export from terrestrial ecosystems is a potentially important flux for the net catchment C balance and links the biogeochemical C cycling of terrestrial ecosystems to their downstream aquatic ecosystems. We have monitored hydrology and stream chemistry over 3 years in ten nested catchments (0.6-15.1 km 2 ) with variable peatland cover (0%-22%) and groundwater influence in subarctic Sweden. Total waterborne C export, including dissolved and particulate organic carbon (DOC and POC) and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 82 publications
9
86
1
1
Order By: Relevance
“…Aquatic export of DOC in peat-dominated catchments is usually strongly promoted by precipitation (Olefeldt et al 2013), similar to what we found in the statistical analysis of catchment DOC export, but in Table 6 the highest absolute DOC export is found in Scotland, which is not the site with the highest annual precipitation. Production of DOC per mm runoff reveals a variation between sites of 7 and 38 mg C mm -1 , where Andøya is found at the lower end.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Aquatic export of DOC in peat-dominated catchments is usually strongly promoted by precipitation (Olefeldt et al 2013), similar to what we found in the statistical analysis of catchment DOC export, but in Table 6 the highest absolute DOC export is found in Scotland, which is not the site with the highest annual precipitation. Production of DOC per mm runoff reveals a variation between sites of 7 and 38 mg C mm -1 , where Andøya is found at the lower end.…”
Section: Discussionsupporting
confidence: 86%
“…The negative effect of current-season's discharge on DOC concentrations agrees with the generally observed diluting effect of precipitation on DOC in peatland runoff, in contrast to upland soil runoff (Köhler et al 2008). A positive relation between discharge and catchment aquatic DOC export is commonly found (Olefeldt et al 2013;Raike et al 2012). Temperature (antecedent and current) promoted DOC export in the autumn and early winter, suggesting that increased microbial activity under higher soil temperatures produces a higher store of potentially leachable DOC (Kalbitz et al 2000;Tipping et al 1999).…”
Section: Discussionsupporting
confidence: 76%
“…Our DOC fluxes are roughly in the same range as those reported from streams in permafrost-affected areas; Carey (2003) reported a flux of 1.6 g C m −2 yr −1 and Petrone et al (2006) reported values between 1.1 and 2.3 g C m −2 yr −1 for three catchments. Our export values are, however, considerably lower than many boreal forest streams (see compilation of DOC export data in Olefeldt et al, 2013).…”
Section: The Relationship Between Doc and Dic Concentrations And Fluxescontrasting
confidence: 60%
“…Flux estimates of DIC from the Scandinavian boreal forest about 700 km south of Abisko in the Krycklan catchment report loads ranging from −0.7 to 1.4 g C m −2 yr −1 ; the negative value indicating a net loss between upstream and downstream measured sites. The DIC export in several sub-catchments of a wetland-influenced catchment in the Abisko area, the Stordalen mire complex, ranged from 0.6 to 3.0 g C m −2 yr −1 (Olefeldt et al, 2013) and the range in yearly DIC export from the Abiskojokken stream (Fig. 6) ranged between 1.5 and 3.2 g C m −2 yr −1 .…”
Section: The Relationship Between Doc and Dic Concentrations And Fluxesmentioning
confidence: 99%
“…Predicting changes in atmospheric carbon dioxide (CO 2 ) and the course of climate change relies on complete and accurate estimates of the sizes and rates of exchange of all global C pools. In addition to global analyses, groundwater C is increasingly implicated in regional C cycling (Genereux et al 2013, Olefeldt et al 2013. Currently, both the size and turnover time of the global groundwater C pool (Cole et al 2007) and the influence of human domestic, industrial, and agricultural groundwater withdrawal on global C cycling are unknown.…”
Section: Introductionmentioning
confidence: 99%